Hubungan Dukungan Sosial dengan Stres Akademik pada Mahasiswa Kedokteran - Fezagustia Rizdanti; Esteria Marhayuni; Sri Maria Puji Lestari; Asri Mutiara Putri (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2022)
The Covid-19 pandemic has caused a change in learning patterns from generally face-to-face either in the university enviroment or in a place of practice, turning into bold or online learning that carried out from their respective homes to fulfill the rights of students to receive education during the pandemic. This learning pattern becomes a separate problem that will trigger the occurrence of academic stress. One of the factors that influence academic stress is social support. Social support is believed to be able to overcome academic stress. The research objectives areThis study aims to determine whether there is a correlation between social support and academic stress in Malahayati medical students during the Covid-19 pandemic. This study uses a quantitative approach with a correlational type of research, using a sampling technique Accidental sampling totaling 121 samples. The research respondents were 121 students with the highest level of social support in the moderate category (67.8%) and the highest level of academic stress in the severe category (54.5%). The results of this study indicate that there is no significantcorrelationbetween social support and academic stress in Malahayati University medical students during the Covid-19 pandemic.